A locked knee in an adolescent boy - Dykes, H. W.; Tytko, J. (The Physician and Sportsmedicine, 2004)
A young athlete presenting with a locked knee is an uncommon occurrence in most outpatient clinics. Locked knees in children are primarily caused by meniscal tears, a discoid meniscus, or osteochondritis dissecans. When diagnosing meniscal tears, the history, physical examination, MRI, and/or arthroscopy are used to support a definitive diagnosis. Arthroscopic surgery is performed with the intention to preserve as much of the nontraumatized meniscus as possible, as in this case of an adolescent whose knee required surgical repair. However, in some cases, a total menisectomy is inevitable.